Usage of Antibiotic on Chicken Poultry in District of Malang, East Java, Indonesia - Zalizar, Lili; Relawati, R.; Pancapalaga, W. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Usage of antibiotics on chicken poultry has been used for long time to control bacterialdiseases. It is easy to obtain antibiotic on the market because there is an aim to increase productivityof livestock-based food quickly. However, it has encouraged the use of drug excessively withoutregard to the security aspect of livestock products produced. This study was conducted to determinethe use of antibiotics on chicken farms in District of Malang. Research subjects were farmers whoapply antibiotics on their chicken poultry. Primary data collection was done with a structuredinterview, and followed by in-depth interview for some key respondents. Secondary data wasobtained from the Central Bureau of Statistics and the Department of Agriculture/AnimalHusbandry, meanwhile data of antibiotic products was derived from drug companies or VeterinaryDrug Association. The research result showed that the majority of chicken farmers in Malang useantibiotics, only a few of them gave Â multi-vitamin/ mineral and herbal medicine. Most farmers usethe same antibiotics for the last 3 years and they determine drug dosage based on average weight ofchicken, consequently a number of bacteria could be resistant to antibiotics, already. If one yearDistrict of Malang requires antibiotic dose of 3.315 billion, the cost required reaches approximatelyRp 2.87 trillion. It needs to guide the farmers to use antibiotics wisely: change antibiotics, determinethe dose and timing of giving antibiotics.Key Words: Antibiotic Usage, Chicken Poultry, Food Safety